2008
DOI: 10.1134/s0006297908040032
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian galectins: Structure, carbohydrate specificity, and functions

Abstract: Galectins are a family of beta-galactoside binding lectins, homological by a sequence of the carbohydrate-binding site. In this review literature data about structure and carbohydrate specificity of galectins are discussed. The role of galectins in the regulation of cell adhesion in immune response, inflammation, and cancer progression is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 92 publications
0
46
0
2
Order By: Relevance
“…It is of interest to note that in a recent study, based on the findings that Gal-7-null mice show a defect in reepithelialization of skin wounds and in the distribution of cortactin (a protein localized at the lamellipodia), it has been suggested that Gal-7 modulates the formation and/or stabilization of lamellipodia (Gendronneau et al, 2008). Although all mammalian galectins specifically recognize galactose-containing glycans, each galectin has fine specificity for more complex glycans, and saccharides in the vicinity of galactose considerably influence the affinity for a given galectin (reviewed by Brewer, 2004;Hirabayashi et al, 2002;Rapoport et al, 2008). For example, the affinity of Gal-1 for the blood group A tetrasaccharide is about 100-fold lower than that for Gal-3 (Sparrow et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note that in a recent study, based on the findings that Gal-7-null mice show a defect in reepithelialization of skin wounds and in the distribution of cortactin (a protein localized at the lamellipodia), it has been suggested that Gal-7 modulates the formation and/or stabilization of lamellipodia (Gendronneau et al, 2008). Although all mammalian galectins specifically recognize galactose-containing glycans, each galectin has fine specificity for more complex glycans, and saccharides in the vicinity of galactose considerably influence the affinity for a given galectin (reviewed by Brewer, 2004;Hirabayashi et al, 2002;Rapoport et al, 2008). For example, the affinity of Gal-1 for the blood group A tetrasaccharide is about 100-fold lower than that for Gal-3 (Sparrow et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…They form a molecular family composed of Ca +2 -independent soluble lectins (also known as galaptins or S-lectins)-defined by a conserved CRD that binds β-galactoside-containing glycans-and present a conserved β-sandwich structure formed by six S1-S6 and five F1-F5 strand sheets. The S4-S6 strands contain the conserved carbohydrate-binding amino acids (Hirabayashi & Kasai, 1993;Loris, 2002;Rabinovich et al, 2007;Rapoport et al, 2008;Rini & Lobsanov, 1999).…”
Section: Galectinsmentioning
confidence: 99%
“…Galectins are components of a lectin family of extensive taxonomic distribution and striking evolutionary conservation, characterized by a conserved carbohydrate recognition domain (CRD) with a relatively high affinity to β-galactosides [22,23]. They are involved in immunity, cell communication, self not-self recognition, cell proliferation, development, differentiation and malignant transformation [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in immunity, cell communication, self not-self recognition, cell proliferation, development, differentiation and malignant transformation [22][23][24][25]. Intracellular galectins participate in a wide variety of biological phenomena, and a single galectin can exert multiple roles [25,26,27].…”
Section: Introductionmentioning
confidence: 99%